Somatic mutations of DICER1 and KMT2D are frequent in intraocular medulloepitheliomas. Issue 5 (4th February 2016) - Sahm, Felix; Jakobiec, Frederick A.; Meyer, Jochen; Schrimpf, Daniel; Eberhart, Charles G.; Hovestadt, Volker; Capper, David; Lambo, Sander; Ryzhova, Marina; Schüller, Ulrich; Zheludkova, Olga; Kumirova, Ella; et al.
Abstract : Intraocular medulloepithelioma (IO‐MEPL) is an uncommon embryonal neuroepithelial neoplasm of the eye. Little is known about the cytogenetics, molecular biology, and pathogenesis of this tumor. In the present study we investigated the mutational landscape of 19 IO‐MEPL using targeted next‐generation sequencing. Routinely prepared paraffin‐embedded samples were assessed with high‐coverage genome sequencing on the Illumina NextSeq 500 platform using a customized gene panel set covering the coding region of 130 genes. This revealed several notable genomic alterations, including mutations of DICER1 (6 tumors) and KMT2D (also known as MLL2 ; 5 tumors)—which are frequently recurrent and mutually exclusive molecular events for IO‐MEPL. Non‐recurrent mutations in the cancer‐associated genes BRCA2, BRCA1, NOTCH2, CDH1, and GSE1 were also identified. IO‐MEPL samples harboring a DICER1 mutation disclosed few chromosomal alterations and formed a separate DNA methylation cluster, indicating potential differences in genetic and epigenetic events arising perhaps from the presence of this aberration in the tumor genome. The high proportion of recurrent somatic DICER1 and KMT2D mutations in this series of sporadic IO‐MEPL points to their likely important roles in the molecular pathogenesis of these rare embryonal tumors, and perhaps suggests the existence of distinct molecular variants of IO‐MEPL. Although the precise role of these recurrent mutations in the development of IO‐MEPL, and their relationship to pro‐oncogenic molecular mechanisms, have yet to be determined, unraveling their roles could eventually be exploited for nonsurgical therapies of these neoplasms. © 2016 Wiley Periodicals, Inc.